UJI AKTIVITAS ANTIJAMUR INFUSA UMBI BAWANG PUTIH (Allium sativum L.) TERHADAP Candida albicans SERTA PROFIL KROMATOGRAFINYA - Khusnul Diana (Universitas Tadulako, 2016)
As traditional medicine, bawang putih or garlic ( Allium sativum L.) can cure as antibacterial and antifungal beside on can restorative as antihypertension, antacid, carminativa (in the dyspepsia), expectorancia and anticolesterol. This research was conducted in order to know the antifungal activity of infusion of Allium sativum against Candida albicans and to identify chemical component’s of this infusion. The antifungal activity was done by liquid dilution method. The MIC (Minimal Inhibitory Concentration) and MFC (Minimal Fungicidal Concentration) value were used as parameter to determine the antifungal activity. Concentration used in this reseach were 17,5%; 16,25%; 15%; 13,75% ; 12,5% dan 11,25% v/v for Candida albicans. The activity was done by incubating the infusion with fungal in CYG DS media of 37ºC for 18-24 hours. Identification of chemical component was carried out by paper chromatography and thin layer chromatography. The result showed that the MIC (Minimum Inhibitor Concentration) for Candida albicans could not be observed because the mixture was turbid. The MFC (Minimum Fungicidal Concentration) for Candida albicans was 15% v/v. The tube test and chromatogram showed that the infusion of Allium sativum contained flavonoid, and saponin.